Financial Development: A Fillip or Impediment to Nigeria’s Economic Growth - Ibrahim, Taofik Mohammed; Shuaibu, Mohammed Isa (International Journal of Economics and Financial Issues, 2013)
Over the years, substantial theoretical and empirical studies have been conducted on the financial development-economic growth nexus. While a strand of the literature has found a positive linkage between this critical nexus, the other suggests otherwise. This study contributes to the debate by examining the finance-growth nexus for Nigeria using the bounds testing approach to cointegration within an ARDL framework proposed by Pesaran et al. (2001) and the augmented Granger causality test developed by Toda and Yamamoto (1995).Empirical evidence reveals that financial development significantly affects economic growth in the short and long run. The major implication for our study therefore is that financial regulatory institutions need to be strengthened to better maximize the gains from financial development especially its role towards real sector development and job creation for the growing population. Keywords: Financial Development; Economic Growth; Co-integration; Causality JEL Classifications: E44; O16; O55